Management of chronic subdural hematoma: Burr hole versus twist drill – A prospective study - Goyal, Ram; Nayak, Biswaranjan; Maharshi, Rajiv; Bidhar, Debadulal; Panchal, Sunil; Pathak, Harish (Asian Journal of Neurosurgery, 2018)
Introduction: Incidence of chronic subdural hematoma (CSDH) is about 5/100,000/year in the general population and still rising. Two surgical techniques, namely, burr-hole evacuation (BHE) versus twist-drill evacuation (TDE) are commonly used to manage such patients but the preferred surgical method continues to attract debate, and the time for an evidence-based approach is now overdue. In vogue with recent trends, a minimally invasive surgical approach is considered as best; therefore, we tried to establish the hypothesis that TDE is as safe and as effective as BHE for CSDH treatment. Materials and Methods: A prospective, randomized, controlled study including forty patients was conducted. The primary outcome variable studied was clinically significant recurrence rate. The secondary outcome variables in postoperative period and follow-up assessment of the patients include Glasgow coma scale (GCS), Markwalder grade, postoperative complication, and operative mortality rate. Results: In our study, results of BHE seem to be superior than TDE in terms of recurrence rate (5% vs. 15%), complication rate (15% vs. 20%), and mean Markwalder neurological grading score and mean GCS at time of discharge (0.16 vs. 0.45 and 14.95 vs. 14.65, respectively). TDE seems to be better than BHE in terms of duration of hospital stay (7.4 vs. 8.05). However, these differences were not statistically significant. TDE is having the advantage of being performed at bedside without the need of monitored anesthesia and anesthetist, time saving, and least invasive. Overall results were comparable across both techniques without any significant difference. Conclusion: Although both techniques appear to be similar in respect of their primary and secondary outcome variables, but TDE is having the advantage of being performed at bedside without the need of monitored anesthesia and anesthetist, time saving, and small incision.
Keywords: Burr hole; chronic subdural hematoma; twist drill